A Survey of Knowledge and Attitude of Hospital Executive Management Team of Abadan and Khorramshahr Hospitals Regarding Hospital Accreditation in 2017 - jamshid Bahmei; Mohammad khavasi; farahnaz salehinia; Rouhollah Rouhandeh; Masoumeh Asadi; sasan ghorbani (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Knowledge and attitude of administrators regarding accreditation play a significant role in its successful implementation. Thus, designing and implementing a survey is necessary to evaluate knowledge and attitudes of hospital executive management teams in the accreditation of Abadan and Khorramshahr hospitals, Iran. Methods: This descriptive cross-sectional study was conducted in the first half of 2017. The statistical population of this study consisted of all members of the executive management teams of Abadan and Khorramshahr hospitals. The sampling method was census-based and the sample size was 46 persons. Data collection was conducted by using a questionnaire. Validity and reliability of the questionnaire were already confirmed. Finally, the data were analyzed by SPSS software using descriptive statistics. Results: More than half of the participants had a great amount of knowledge about the requirements, goals, principles, and concepts of accreditation standards, as well as the need to participate in accreditation courses. More than 50% of the participants also had high expectations and positive attitudes towards the impact of accreditation on increasing public trust, improving the face of hospital, enhancing service quality, increasing patient satisfaction, raising safety and services, and improving hospital processes. There was a non-significant relationship between knowledge and attitude among the participants. Conclusion: Regarding the average awareness of hospital managers about accreditation, education and awareness-raising among them seems to be necessary. Considering the high score of managers' attitudes and expectations regarding accreditation, the process of accreditation in these hospitals is hoped to be more effective, such that it will result in higher patient safety and satisfaction.